2005
DOI: 10.1128/jvi.79.19.12455-12463.2005
|View full text |Cite
|
Sign up to set email alerts
|

Virion Envelope Content, Infectivity, and Neutralization Sensitivity of Simian Immunodeficiency Virus

Abstract: A truncating E767stop mutation was introduced into the envelope glycoprotein of simian immunodeficiency virus (SIV) strain SIV239-M5 (moderately sensitive to antibody-mediated neutralization and lacking five sites for N-linked carbohydrate attachment) and strain SIV316 (very sensitive to neutralization, with eight amino acid changes from the neutralization-resistant parental molecular clone, SIV239). The truncating mutation increased Env content in virions, increased infectivity, and decreased sensitivity to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
68
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 58 publications
10
68
2
Order By: Relevance
“…We demonstrated that the cytoplasmic tail can modulate sensitivity to neutralization, in agreement with other studies (12,16,32,34). Furthermore, we were able to identify four amino acids in the LLP-2 domain that affect both neutralization and infectivity.…”
Section: Discussionsupporting
confidence: 79%
“…We demonstrated that the cytoplasmic tail can modulate sensitivity to neutralization, in agreement with other studies (12,16,32,34). Furthermore, we were able to identify four amino acids in the LLP-2 domain that affect both neutralization and infectivity.…”
Section: Discussionsupporting
confidence: 79%
“…That the density of Env had a limited effect on the neutralization sensitivity of virions using diverse bnAbs was unexpected as a prior study had shown that SIV was more resistant to neutralizing antibodies with an increase in Env copy number (13). However, in that study truncations in the CTT of SIV gp41 had strong effects on infectivity and so might have altered Env conformation and/or stability.…”
Section: Discussionmentioning
confidence: 44%
“…With HIV-1, however, manipulating the CTT has either enhanced Env modestly (i.e., 3-fold) or decreased its levels (11). CTT modification also affects the antigenicity of HIV-1 Env (12) and can alter neutralization sensitivity in an Env-dependent manner (13)(14)(15)(16)(17). Stable cell line production of Env (18), and substitutions with a foreign TM domain have been shown to enhance Env on virus-like particles (VLPs); but the effects are either modest, or the reports lack details about the integrity, function, and antigenicity of trimeric Env (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Reports suggest that truncation of gp41 cytoplasmic tail increases virion incorporation of Env, which may enhance viral replication in macrophages by increased fusion activity (24)(25)(26). Although the mutations in the present study (I805T, I828R, T829A, and V878I) did not result in truncation, they affected the cytoplasmic tail of gp41.…”
Section: Assessment Of Virion-incorporated Env Levelscontrasting
confidence: 49%